An Expert System Using Certainty Factor for Determining Insomnia Acupoint - Elizabeth Paskahlia Gunawan; Retantyo Wardoyo (IJCCS (Indonesian Journal of Computing and Cybernetics Systems), 2018)
In treating insomnia patients, acupuncturists who are not always in their clinics trust their patients to their assistants but because of their assistants limited knowledge, their assistants can not determine the right acupoints. Therefore, an application that able to store their knowledge about insomnia disease treatment is needed so that their assistants can handle the patients like they do.